Penyuluhan Ibu Hamil untuk Persiapan Persalinan “PAMIL SALIN” di Puskesmas Babirik - Dewi, Puspita; Haryono, Ika Avrilina; Nurliani, Siti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Many mothers feel anxious and unprepared for childbirth, which can have an impact on their mental and physical health. By improving counseling programs, it is hoped that pregnant women can better understand various aspects of childbirth, reduce anxiety, and improve their mental and physical readiness. The method of implementing the activity is by holding meetings with the community to attend counseling for pregnant women to prepare for childbirth at the Babirik Health Center. This activity was carried out in September 2024 at the Babirik Health Center, Hulu Sungai Utara Regency, South Kalimantan Province. The community service activities carried out through counseling for pregnant women to prepare for childbirth at the Babirik Health Center showed positive results in increasing the knowledge, skills, and readiness of pregnant women in facing childbirth. Overall, this counseling program has succeeded in achieving several main objectives, although there are still several challenges that need to be overcome to increase its effectiveness.